Customer preferences in car design using kansei engineering and cubic Bezier curve - W N, Hidayah; S H, Yahaya; H, Sihombing; M. S., Salleh; A, AbuAbdullah (International Journal of Engineering and Technology, 2018)
This study is focused on fulfilling the customer’s needs and also the organizations’ need to organize their genuine phenomenal awareness to find out the customer outline inclinations before creating a specific item since customer design has turned into the essential worry of the organizations' technique. This study is to recognize and analyze the customers’ preferences through car design by using mathematical con-cept known as Bézier curves. The approach is utilized as a part of the study to distinguish and study the consumer loyalty through the cus-tomer’s preferences in designing a car. The cars are then categorized into two types which City cars and Sedan cars. These categories are controlled by the eight segments of cubic Bézier function. The customer’s preferences towards car design can be denoted through the use of cubic Bézier curves.